Skip to main content

Gauss's quote for positive, negative, and imaginary number

Recently I watched the following great videos about imaginary numbers by Welch Labs.

https://youtu.be/T647CGsuOVU?list=PLiaHhY2iBX9g6KIvZ_703G3KJXapKkNaF

I like this article about naming of math by Kalid Azad.

https://betterexplained.com/articles/learning-tip-idea-name/

Both articles mentioned about Gauss, who suggested to use other names of positive, negative, and imaginary numbers. Gauss wrote these names are wrong and that is one of the reason people didn't get why negative times negative is positive, or, pure positive imaginary times pure positive imaginary is negative real number. I made a few videos about explaining why -1 * -1 = +1, too.

Explanation: why -1 * -1 = +1 by pattern
https://youtu.be/uD7JRdAzKP8

Explanation: why -1 * -1 = +1 by climbing a mountain
https://youtu.be/uD7JRdAzKP8

But actually Gauss's insight is much powerful. The original is in the Gauß, Werke, Bd. 2, S. 178.
Hätte man +1, -1, √-1) nicht positiv, negative, imaginäre (oder gar ummögliche) Einheit, sondern etwa directe, inverse, laterale Einheit gennant, so hätte von einer solchen Dunklelheit kaum die Rede sein können.
 If I translate this to English:
If we call +1, -1, and √-1 had been called direct, inverse and lateral units, instead of positive, negative, and imaginary (or impossible) units, such an obscurity would have been out of the question.
Gauss suggested negative should be coined as inverse. So inverse times inverse is direct, like Kalid coined positive and negative as forward and backward. If you do inverse and then inverse, of course it is original direction, like backward and then backward is forward.

Gauss's imaginary number name is lateral number (side number). When direct lateral times direct lateral, which is √-1 * √-1 = -1, then -1 * √-1 is inverse lateral, - √-1, then inverse lateral * direct lateral is direct, -√-1 * √-1 = +1. You can see in the following figures.


Figure 1: Inverse and direct instead of positive and negative

Figure 2: direct, inverse, and lateral
In this terminology, not ``negative times negative is positive.'', but ``inverse times inverse is direct.''

Comments

Padminiprwatech said…
Data science is one of the top course in today's career. Your content will going to helpful for all the beginners who are trying to find What is the Sample Variance. Thanks for sharing useful information. keep updating.

Popular posts from this blog

Why A^{T}A is invertible? (2) Linear Algebra

Why A^{T}A has the inverse Let me explain why A^{T}A has the inverse, if the columns of A are independent. First, if a matrix is n by n, and all the columns are independent, then this is a square full rank matrix. Therefore, there is the inverse. So, the problem is when A is a m by n, rectangle matrix.  Strang's explanation is based on null space. Null space and column space are the fundamental of the linear algebra. This explanation is simple and clear. However, when I was a University student, I did not recall the explanation of the null space in my linear algebra class. Maybe I was careless. I regret that... Explanation based on null space This explanation is based on Strang's book. Column space and null space are the main characters. Let's start with this explanation. Assume  x  where x is in the null space of A .  The matrices ( A^{T} A ) and A share the null space as the following: This means, if x is in the null space of A , x is also in the null spa

left-associative and right-associative

Japanese version I forget to explain one rule that function application is ``left-associative.'' f x y = (f x) y, The function is processed from left to right. For example, 1 - 2 - 3 is not a λ expression, but it is a left-associative example , means (1 - 2) - 3. Enclosed by parentheses '()' is calculated first. Therefore, 1-2-3 = (1-2)-3 = -1-3 = -4. If this is right-associative, 1-2-3 = 1-(2-3) = 1-(-1) = 2. Please note the answer is different. If we write this function as a λ expression, (λx. λy. λz. x - y - z) 1 2 3 This concludes (λ x. λy. λz. x - y - z) 1 2 3 ... apply x to 1 = (λ y . λz. 1 - y - z) 2 3 ... apply y to 2 = (λ z. 1 - 2 - z) 3 = (λ z . -1 - z) 3 ... apply z to 3 = -1 - 3 = -4. x = 1, y = 2, and z = 3 if this is left-associative and x = 3, y = 2, and z = 1 if this is right-associative. We use left-associative in λ calculus unless it is explicitly mentioned.